Rethinking Risk in National Security Lessons of the Financial Crisis for Risk Management - Mazarr, Michael J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book examines the role of risk management in the recent financial crisis and applies lessons from there to the national security realm. It rethinks the way risk contributes to strategy, with insights relevant to practitioners and scholars in national security as well as business. Over the past few years, the concept of risk has become one of the most commonly discussed issues in national security planning. And yet the experiences of the 2007-2008 financial crisis demonstrated critical limitations in institutional efforts to control risk. The most elaborate and complex risk procedures could not cure skewed incentives, cognitive biases, groupthink, and a dozen other human factors that led companies to take excessive risk. By embracing risk management, the national security enterprise may be turning to a discipline just as it has been discredited.
1. Risk, Judgment and Uncertainty -- 2. Defining Risk -- 3. Approaches to Risk in National Security -- 4. Risk and Uncertainty -- 5. Risk is What We Make of It -- 6. Indifferent to Consequences -- 7. The Swans to Worry About Are Gray -- 8. Risk Becomes Personalized -- 9. What You Don$1 (Bt Know Can Destroy You: Ignorance and Correlated Risk -- 10. Risk, Incentives and Culture -- 11. The Role of Risk in Strategy -- 12. Outcome Assessment of the Emerging U.S. National Security Strategy -- 13. Principles of Effective Risk Management -- 14. Managing Uncertainty.s
Keywords: Political science; Risk management; Political theory; Comparative politics; Politics and war; Statistics; Behavioral economics; Political Science and International Relations; Military and Defence Studies; Risk Management; Political Theory; Comparative Politics; Statistics for Business/Economics/Mathematical Finance/Insurance.; Behavioral/Experimental Economics; Electronic books